2015
DOI: 10.1002/art.39289
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Heterogeneity of Skin Gene Expression Patterns in Systemic Sclerosis

Abstract: Objective To examine the heterogeneity of global transcriptome patterns in systemic sclerosis (SSc) skin in a large sample of patients with SSc and control subjects. Methods Skin biopsy specimens obtained from 61 patients enrolled in the Genetics versus Environment in Scleroderma Outcome Study (GENISOS) cohort and 36 unaffected control subjects with a similar demographic background were examined by Illumina HumanHT-12 bead arrays. Followup experiments using quantitative polymerase chain reaction and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
144
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(170 citation statements)
references
References 43 publications
25
144
1
Order By: Relevance
“…Given the repeatedly observed clinical and molecular heterogeneity in SSc patients across multiple independent cohorts (8,(10)(11)(12), the robustness of the SSc signatures identified in our analysis is unexpected and significant. Until now, the lack of such a robust signature has hampered development of novel diagnostics and prognostics for monitoring SSc patients in clinics.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Given the repeatedly observed clinical and molecular heterogeneity in SSc patients across multiple independent cohorts (8,(10)(11)(12), the robustness of the SSc signatures identified in our analysis is unexpected and significant. Until now, the lack of such a robust signature has hampered development of novel diagnostics and prognostics for monitoring SSc patients in clinics.…”
Section: Discussionmentioning
confidence: 73%
“…We identified 4 clinical microarray gene expression datasets from the NCBI's Gene Expression Omnibus (GEO) database comprising 282 samples obtained from skin ( Figure 1 and Supplemental Table 1; supplemental material available online with this article; doi:10.1172/jci.insight.89073DS1) (7,(10)(11)(12), which were derived from healthy control subjects, patients with diffuse cutaneous SSc or limited cutaneous SSc, and with various disease duration. Two of these datasets profiled longitudinally collected samples from study participants during treatment with rituximab (10) and nilotinib (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these mediators, the interferons (IFNs) have captured the most attention due to their central role in regulating a multitude of biological functions in the innate immune system, facilitating their primarily antiviral activity [4,5]. Microarray and proteome-wide studies largely documented the presence of BIFN signatures^as a common This article is part of the Topical Collection on Scleroderma theme in most of the organs involved in SSc, such as skin, lungs, and peripheral blood mononuclear cells (PBMCs) [2,3,[6][7][8][9][10][11]. In vitro studies showed that activation of the innate immune response in immune and non-immune cells, including fibroblasts and endothelial cells (ECs), by specific TLR ligands, induced high expression of several IFN-and TGFβ-responsive genes also seen upregulated in SSc skin, such as CXCL9, OAS2, PAI-1, and ET-1 [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is an increased relative risk of SSc in first degree relatives of patients with the condition and a number of human leukocyte antigens are associated with SSc, several of which correlate with specific ethnic populations or clinical features (1). Genomic analyses can differentiate normal from scleroderma skin and disclose associated fibroinflammatory and interferon (IFN)-associated gene signatures (2, 3). Among the chemokines, CXCL4 has been shown to predict the risk and progression of SSc (4).…”
Section: Pathogenesis Of Sclerodermamentioning
confidence: 99%